ZmMATE6 from maize encodes a citrate transporter that enhances aluminum tolerance in transgenic Arabidopsis thaliana. (October 2021) - Du, Hanmei; Ryan, Peter R.; Liu, Chan; Li, Hongjie; Hu, Wanpeng; Yan, Weina; Huang, Ying; He, Wenzhu; Luo, Bowen; Zhang, Xiao; Gao, Shibin; Zhou, Shufeng; et al.
Highlights: ZmMATE6 gene from maize was cloned and transformed into Arabidopsis thaliana. Overexpression of ZmMATE6 in Arabidopsis resulted in enhancing the resistance to Al. Transgenic Arabidopsis exhibited increased citrate exudation and decreased Al accumulation in roots. The loss of function caused by the substitution of the fifth residue of CEM domain may also be related to other factors. Abstract: The yields of cereal crops grown on acidic soils are often reduced by aluminum (Al) toxicity because the prevalence of toxic Al 3+ cations increases as pH falls below 5.0. The Al-dependent release of citrate from resistant lines of maize is controlled by ZmMATE1 which encodes a multidrug and toxic compound extrusion (MATE) transporter protein. ZmMATE6 is another member of this family in maize whose expression is also increased by Al treatment. We investigated the function of this gene in more detail to determine whether it also contributes to Al resistance. Quantitative RT-PCR measurements found that ZmMATE6 was expressed in the roots and leaves of Al-resistant and sensitive inbred lines. Treatment with Al induced ZmMATE6 expression in all tissues but several other divalent or trivalent cations tested had no effect on expression. This expression pattern and the induction by Al treatment was confirmed in ZmMATE6 promoter–β-glucuronidase fusion lines. Heterogeneous expression of ZmMATE6 displayed a greater Al-activated release of citrate from the roots and was significantly resistant to Al toxicity than controls. This was associated with reduced accumulation of Al in the root tissues. Our results demonstrated that ZmMATE6 expression is induced by Al and functions as a citrate transporter.